The Aptitude of Universitas Pendidikan Indonesia Students in Designing Science Learning that Integrates Culture - Sri Wuryastuti; Ari Widodo; Encep Supriatna; Muhammad Hanif; Fitri Alfarisa; Ita Rustiati Ridwan (Postgraduate, University of Mataram, 2023)
The aim of this research is to describe how the aptitude of elementary school students in designing a learning that integrates culture. The research methodology that was used in this research was descriptive qualitative by analysing each components of the learning plans that was designed by elementary school teacher matriculant of seventh semester who enrolled in a course namely scienceÂ learning based on Banten culture that consists ofÂ 30 females and 15 males. The result of the study showed that the studentsâ€™ aptitude in designing science learning that integrates culture in elementary school is categorised as good with average overall score for each lesson plan components of 3,13. The research result was categorised as good because before designing the lesson plan the students have already had rich experiences towards local wisdom contents related to the course material, especially science through lectures. This research gave impacts in developing students aptitude in designing lesson plan that integrated cultures which can be their provision when they become elementary school teachers so that can also give impact for the elementary school students to know more about their cultures which is wrapped in a form of science.